Accuracy of Orthodontic Indirect Bracket Bonding by CAD/CAM Transfer Tray - Mahran, Ahmed; Refai, Wael Mohamed Mobarak; Abdelhameed, Ahmed Nasef; Hashem, Ahmed Shawky (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: Indirect bonding is a technique in which orthodontic attachments are transferred from dental casts (working models) and bonded onto dentition using a transfer tray. Indirect bonding is a preferred technique for many orthodontists as it is less time consuming compared to direct bonding. Evolution in technology allowed forming transfer trays digitally by the integration of computer-aided design and computer-aided manufacturing (CAD/CAM). This study was conducted to measure transfer accuracy of CAD/CAM indirect three dimensional printed bonding trays. Materials and methods: 140 teeth (all upper and lower incisors, canines and premolars) in 7 patients were bonded by vacuum-formed transfer tray formed on 3 dimensional (3D) printed models with resin brackets. Intra oral scanner was used initially to obtain stereolithographic file for virtual brackets positioning and another scan was taken after brackets bonding. Superimposition of virtual STL files and post bonding STL files was done by Geomagic Qualify software to measure linear and angular deviation of brackets positions. Results: One sample t-test was performed to determine whether the mean transfer error was statistically within the selected acceptable limits of 0.5 mm for linear measurements. P-values of less than 0.05 indicated differences within the limits of 0.5 mm for linear measurements. All brackets were transferred within the accepted deviation limits Conclusions: CAD/CAM designed and printed transfer trays had high transfer accuracy in linear measurements in all teeth.